Penerapan Metode Analitycal Hierarchy Process (AHP) Dalam Menentukan Siswa Berprestasi SMA MAN Simalungun - Bonita, Tanti; Irawan, Eka; Rizki, Fitri (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The purpose of this study was to make a ranking of high achieving students in the tenth grade at Simalungun MAN School. In this study, researchers used a Decision Support System, using the Analytical Hierarchy Process (AHP) Method. From the data of student grades, all tenth graders of MAN Simalungun obtained student scores that have not yet reached the minimum completeness criteria (KKM). To assess student achievement not only from semester exam scores, grades in other fields can also be considered by teachers in assessing students. In the assessment can be taken from everyday values and also student absences. It is hoped that the results of this research can provide input to the school, especially teachers to pay more attention to students who are weak in the learning process. So students are motivated and can improve achievement at school